Study of the Antihypertensive Peptides Derived from Alpha-Lactalbumin Hydrolysate after Simulation of Digestion - Antonella Alba; Jessica Báez; Adriana Maite Fernández-Fernández; Agustina Nardo; María Cristina Añón; Alejandra Medrano; Margot Paulino (Biology and Life Sciences Forum, 2022)
Alpha-lactalbumin is a whey protein that is a cheese-making industrial residue of high biological value. The antihypertensive capacity of three peptides obtained from the simulated gastrointestinal digestion of alpha-lactalbumin hydrolysates was studied. The alpha-lactalbumin hydrolysis was performed using the Alcalase enzyme and was subsequently subjected to a simulated digestion process using pepsin and pancreatin enzymes to mimic digestion conditions. The peptides were identified from a RP-HPLC fractionation of the digest and subsequent identification by mass spectrometry analysis. Three peptides from the alpha-lactalbumin sequence were obtained: IWCKDDQNPH (P1), KFLDDDLTDDIM (P2), and DKFLDDDLTDDIM (P3). The in vitro antihypertensive activity of the peptides was determined by studying the inhibition of the angiotensin-converting enzyme, with P1 being the only peptide with antihypertensive activity detected by this methodology (IC50 = 3.91 ± 0.2 mg/mL). In order to correlate the structural (molecular dynamics simulations) and physicochemical properties with potential mechanisms of antihypertensive capacity, in silico methods were performed. The peptides P1, P2, and P3 had a negative global charge and were hydrophilic. After molecular modeling, the peptide structures were submitted to a refinement based on an energy minimization and further molecular dynamics simulation to assess their global size and conformational space. After a 50-nanosecond simulation, the global structures, solvated and immersed in an ionic water solution similar to that of blood, were studied in their solvent-accessible surfaces. A secondary structure (alpha-helix) was observed in the P1 peptide, but in general, all peptides showed an extended folding. The surfaces were charge code colored and in a visual inspection it could be conjectured that all of them exposed the charge, mainly a negative charge, to the solvent surface, in agreement with the GRAVY index, which was also evaluated. In conclusion, the structure and amino acid composition of peptide 1 assessed by in silico studies agrees with the antihypertensive activity obtained by the in vitro study.